Front Cover: The Impact of Lithium Tungstate on the Densification and Conductivity of Phosphate Lithium‐Ion Conductors (ChemElectroChem 5/2022). Issue 5 (1st February 2022) - Odenwald, Philipp; Ma, Qianli; Davaasuren, Bambar; Dashjav, Enkhtsetseg; Tietz, Frank; Wolff, Michael; Rheinheimer, Wolfgang; Uhlenbruck, Sven; Guillon, Olivier; Fattakhova‐Rohlfing, Dina
Abstract : The Front Cover shows LATP powder and a dense LATP pellet obtained after powder sintering, which typically requires high temperatures. With only a small weight fraction of Li2 WO4, a significant reduction in sintering temperature and increase in ionic conductivity can be achieved. Processing and performance improvements render Li2 WO4 a very promising sintering aid for the development of LATP‐based solid‐state batteries like the pouch cell also shown in the cover picture. More information can be found in the Research Article by P. Odenwald et al .